Self-Disclosure of Mothers to Their Non-Marital Children - Sintawati, Sintawati; Safitri, Jehan; Akbar, Sukma Noor (Jurnal Kognisia, 2021)
Pregnancy outside of marriage is counsidered to be embarassing socially, culturally and even religiously in Indonesian society. it becomes difficult when a mother, who had non-marital pregnancy, wants to reveal the information about herself to non-marital child. in this case there is a dilemma for self-disclosure. on the one hand it is very important for the mother to disclose herself. however, on other hand, there are several risks that will be faced by the parent when revealing the fact that she  was pregnant outside of marriage. the purposes of this study were to find out the aspects influencing the self-disclosure of the mothers ti their non-marital children and the factors influencing the self-disclosure. a qualititative research design using a case stidy approach was employed in this study. the subjects were to the mothers (N and M), who had been pregnant outside of marriage, perfoming self-disclosure to their non-marital children. they were selected using purposive sampling technique. data were collected and extracted using observation  and interview methods. the result of the study was the process of self-disclosure viewed from the aspects of accuary, motivation, time, intensity, and depth and breadth. it was aslo viewed from the influencing factors, namely reciprocity, norm, trust, relationhip quality and gender, which showed that both subject, N and M, perfomed self-disclosure in a similar way and their self-disclosure was carried out by including the influencing aspects and factors.